Analisis Alasan Turki Melakukan Pembelian Senjata S-400 Rusia - Sinaga, Indah; Parameswari, A.A Ayu Intan; Suwecawangsa, Adi (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
This research aims to explain Turkey's reason for purchasing Russian S-400 missile weapons in 2017, amidst its existence as a member of NATO and must be faced with CAATSA sanctions. Turkey’s decision to purchase S-400 Russia Missile weapons is classified as a unilateral act which actually violates the alliance agreement with the United States. While, on the other hand, the realization for joining the purchase of Russian S-400 Missile weapons seen necessary to make a huge influence in relation to Turkish and Russian relations in the future. Therefore, this Thesis will try to answer the question: